Unmanned aerial vehicle system integrating high‐resolution sensors for detecting leaks in irrigation canals—Proof of concept. (8th September 2021) - Traore, Seydou; Fipps, Guy; Swanson, Charles; Dufek, Jan; Robin, Murphy
Abstract: A system for the remote detection of water leaks in irrigation canals is presented which integrates visual, thermal, and multispectral imagers into a specially designed platform mounted on small unmanned aerial vehicles (UAV), along with an image processing and analysis procedure employing three different software packages and customized scripts. The end results are processed images of different colour bands and indexes which are shown to be effective at highlighting the leaks' signatures. A custom payload platform weighing 1 kg was designed and built, consisting of high‐resolution thermal, multispectral, and visual cameras, GPS units, a flight control camera, and a data acquisition system. A total of 27 flights in 4 irrigation districts were conducted to test and evaluate the payload platform and image processing system. The portable platform was successfully flown on three different UAV. A total of 46, 387 images were captured and processed. The image processing and analysis system worked well and identified all known leaks, as well as leaks that the district's staff were unaware of. Thermal image indexes were effective at showing cold spots which were caused by canal leaks. The visual and the blue and green near‐infrared indexes were also found to be effective at identifying leaks. The Normalized Difference Vegetation Index (NDVI) did help differentiate between vegetation and wet soils, but we did not obtain consistent results with the NDVI. Résumé: Un système de détection à distance des fuites d'eau dans les canaux d'irrigation est présenté, qui intègre des caméras dans le domaine du visible, thermiques et multispectrales dans une plate‐forme portable spécialement conçue pour être montée sur des drones aériens sans pilote pour collecter les images, avec une procédure de traitement et d'analyse d'images employant trois différents logiciels et codes personnalisés. Les images traitées obtenues des différentes bandes de couleurs et indices se sont révélées efficaces en mettant en évidence des signes des fuites d'eau sur les images. Une plateforme de charge utile personnalisée pesant 1 kg a été conçue et construite, comprenant des caméras thermiques, multispectrales et visuelles à haute résolution, des unités GPS, une caméra de contrôle de vol et un système d'acquisition de données. Un total de 27 vols ont été effectués dans 4 districts d'irrigation pour tester et évaluer la plate‐forme de collecte et le système de traitement des images. La plateforme portable a été utilisée avec succès sur trois drones différents. Au total, 46, 387 images ont été capturées et traitées. Le système de traitement et d'analyse des images a bien fonctionné et a identifié toutes les fuites d'eau connues, ainsi que les fuites inconnues dont le personnel du district n'était pas au courant. Les indices des images thermiques étaient les plus efficaces pour déterminer les « points froids » sur les images causés par des fuites d'eau de canal. Les indices visuels et les images infrarouges bleu et vertes se sont également avérés efficaces pour identifier les fuites. Le NDVI a aidé à différencier la végétation des sols humides dans certains cas, mais nous n'avons pas obtenu de résultats cohérents avec le NDVI.